Comparative cytogenetic within Achillea genus (Asteraceae) in Iran: I. chromosome number and morphology - Javadi, Hamideh; Shanjani, Parvin Salehi (Acta Biologica Szegediensis, 2022)
The cytological features including chromosome numbers and detailed chromosome measurements of 46 populations of ten Achillea species (A. aleppica, A. bibersteinii, A. eriophora, A. filipendula, A. millefolium, A. nobilis, A. pachycephala, A. tenuifolia, A. vermicularis, and A. wilhelmsii) were reported from Iran. Sample plants and seeds were collected from diff erent geographical regions of Iran. Total chromosome length, long/ short arm ratio, centromere index, total form percentage, inter and intra-chromosomal index, diff erent relative lengths of the mitotic chromosomes were calculated. The populations showed one basic chromosome number x = 9 with two ploidy levels (2x and 4x). The chromosome numbers of A. filipendula, A. nobilis and A. pachycephala, for the first time are new to science and new ploidy levels are reported for A. biebersteinii (4x) and A. wilhelmsii (2x). The mean of chromosome length ranged from 3.8 μm in A. millefolium from Semnan, Chasham, Sirat to 6.37 μm in A. nobilis from Golestan, Agh Emam. Karyotype analysis indicated that chromosomes of Achillea taxa have predominantly median and sub-median centromeres. Several karyological aspects of these taxa are discussed in the light of the cytogenetic data.